2010
DOI: 10.1515/cclm.2010.230
|View full text |Cite
|
Sign up to set email alerts
|

Increased serum concentrations of visfatin and its production by different joint tissues in patients with osteoarthritis

Abstract: These results suggest that visfatin may be involved in the pathophysiology of OA and may have local effects in the joint during the process of OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
48
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 28 publications
(36 reference statements)
0
48
0
1
Order By: Relevance
“…Adipokines, such as interleukin-6 (IL-6), leptin, adiponectin, resistin and visfatin, belong to the family of white-adipose-tissue-produced factors involved in modulating immune and inflammatory responses [10,27] and are present in synovial fluid (SF) of patients with OA [5,8,11,13,19,22]. Very few studies have investigated the relationship between these adipokines and patient-reported joint pain [9,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Adipokines, such as interleukin-6 (IL-6), leptin, adiponectin, resistin and visfatin, belong to the family of white-adipose-tissue-produced factors involved in modulating immune and inflammatory responses [10,27] and are present in synovial fluid (SF) of patients with OA [5,8,11,13,19,22]. Very few studies have investigated the relationship between these adipokines and patient-reported joint pain [9,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, visfatin has also been related with the disease. It was reported that visfatin is significantly increased in the serum of OA patients compared with healthy controls [39]. Likewise, the concentration of visfatin was also increased in the SFL of OA patients compared to controls [40], with levels reportedly higher in SFL compared with to serum in paired samples [39].…”
Section: Visfatin In Rheumatoid Arthritis (Ra)mentioning
confidence: 97%
“…It was reported that visfatin is significantly increased in the serum of OA patients compared with healthy controls [39]. Likewise, the concentration of visfatin was also increased in the SFL of OA patients compared to controls [40], with levels reportedly higher in SFL compared with to serum in paired samples [39]. Moreover, it has been suggested that visfatin might contribute to cartilage degradation since its SFL concentration positively correlates with KellgrenLawrence score and with cartilage degradation biomarkers namely: C-terminal telopeptide of collagen type II (CTX-II), and two degenerative fragments of aggrecan: AGG1 (G1-1H11), and AGG2 (6D6-G2) [40].…”
Section: Visfatin In Rheumatoid Arthritis (Ra)mentioning
confidence: 99%
See 1 more Smart Citation
“…Nampt expression is up-regulated in a variety of acute and chronic inflammatory diseases including acute lung injury [14], sepsis [15], inflammatory bowel disease, [16,17] atherosclerosis, [18,19] osteoarthritis [20][21][22] and rheumatoid arthritis [17,[23][24][25][26][27][28][29][30]. Recent findings have demonstrated that targeted inhibition of Nampt attenuates the inflammatory process and disease progression in mouse models of arthritis [31,32], suggesting that Nampt plays a key role in the pathogenesis of RA.…”
Section: Introductionmentioning
confidence: 99%